Effects of filtered cathodic vacuum arc deposition (FCVAD) conditions on photovoltaic TiO2 films - C. Aramwit (2018)
Titanium dioxide (TiO 2 ) films for photovoltaic applications were synthesized using filtered cathodic vacuum arc deposition (FCVAD) technique. Various deposition conditions were tested for an optimal film formation. The conditions included the oxygen (O 2 ) pressure which was varied from a base pressure 10 -5 to 10 -4 , 10 -3 , 10 -2 and 10 -1 Torr, sample holder bias varied using 0 or -250 V, deposition time varied from 10, 20 to 30 min, and deposition distance varied from 1 to 3 cm. The deposited films were also annealed and compared with unannealed ones. The films under various conditions were characterized using optical microscopy, scanning electron microscopy (SEM), atomic force microscopy (AFM), energy-dispersive X-ray spectroscopy (EDS) and Raman spectroscopy techniques. The film transparency increased and thickness decreased to a nanoscale with increasing of the O 2 pressure. The transparent deposited films contained stoichiometric titanium and oxygen under the medium O 2 pressure. The as-deposited films were TiO 2 containing some rutile but no anatase which needed annealing to form. © 2014 Elsevier B.V.